Development of an Online-Based Management System to Facilitate School Events - Hendi Sama; Indasari Deu; Surya Tjahyadi; Eryc Eryc; Endy Endy (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Web event management is an event arrangement with a web-based system so that it can be accessed on browsers that have been connected to the internet. Along with the development of information systems, events that are running can be developed in the field of systems, namely by designing a system specifically for this event arrangement. The designer has designed a web-based system for Festival Seni Budaya Kasih Semesta as a medium for an event to take place so that the event can run smoothly. In designing the system, the designer uses the Dynamic System Development Method as a research method to analyze and plan a web event design schedule. The framework used is Laravel framework, then the software used in system design is PHP, HTML, CSS, Javascript, MySQL Database. With the DSDM research method and Laravel framework, it is expected to be able to arrange system design efficiently and effectively. With this web event management system, it can help the committee or event participants of Festival Seni Budaya Kasih Semesta to attend the event smoothly